Association between RC/HDL-C and hyperuricemia in adults: evidence from NHANES 2005-2018 - Tai, Yanghao; Chen, Bin; Kong, Yingming; Wang, Xuening (Frontiers in Endocrinology, 2025)
BackgroundThe incidence of hyperuricemia is growing in the world, with a significant influence on the survival and healthy condition of the patient. The connection between serum residual cholesterol (RC) to high-density lipoprotein cholesterol (HDL-C) ratio and hyperuricemia is uncertain. Consequently, we tried to elucidate the connection between the hyperuricemia and RC/HDL-C ratio.MethodsBased on the National Health and Nutrition Examination Survey (NHANES) database, data from 2005 to 2018 were utilized in this cross-sectional research. RC/HDL-C index was calculated by (TC - HDL-C - LDL-C)/HDL-C. Participants were diagnosed with hyperuricemia when the serum uric acid concentration reached 6 mg/dL in women and 7 mg/dL in men. Our researcher utilized smoothed curve fitting and multivariate logistic regression analysis to examine between RC/HDL-C and hyperuricemia among adults. The consistency of these results was examined in various population subgroups.Results2376 individuals (19.1%) were stratified into the hyperuricemia group. We observed statistically significant differences (P values < 0.05) in the hyperuricemia population for remaining variables, except for economic level and alcohol drinking. After correcting for potential confounders, our researchers discovered the strong positive connection between the RC/HDL-C and the possibility of incurring hyperuricemia. The incidence of RC/HDL-C elevated by 98% with each additional unit of the RC/HDL-C. Subgroup analyses showed correlations for the majority of subgroups remained stable. However, gender and several diseases may modify this association.ConclusionsHigher RC/HDL-C is correlated with higher prevalence rate of developing hyperuricemia. However, further research is still required to confirm the causal association.